Challenges of Diagnosis and Management of Complex Febrile Seizures in Infants: A Case Study - Adella Syafira Habsari; Kahayana, Harancang Pandih (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2024)
Background: Complex febrile seizures (KDK) are a type of febrile seizure that is more severe than simple febrile seizures (KDS), characterized by longer duration, recurrence within 24 hours, and/or focal onset. KDK can be a diagnostic and therapeutic challenge, especially in infants. Case presentation: This case report presents a 1-year-old baby girl who was treated in the emergency department (ER) with complaints of recurrent seizures and persistent fever. Physical examination revealed fever and tachypnea, while laboratory examination revealed hyperglycemia, hyperkalemia, hyponatremia, and decreased hematocrit. The patient's history indicated previous episodes of febrile seizures, but no significant family history. Conclusion: The patient was diagnosed with KDK and given fluid resuscitation, antipyretics, anticonvulsants, and antibiotics. The patient's parents are educated about KDK and its management. The patient's prognosis is considered good, with a small chance of long-term neurologic sequelae if treated appropriately.